Acculturation Orientations Toward Two Majority Groups: The Case of Palestinian Arab Christian Adolescents in Israel - Horenczyk, Gabriel (Journal of cross-cultural psychology, 2007)
This study employs an expanded conceptualization and methodology of acculturation orientations to examine the identity and acculturation patterns of Palestinian Arab Christian adolescents in Israel, who can be seen as a “double minority”—Arabs in the midst of the majority Jewish population and Christians within Israel's dominantly Muslim Arab society. We examined the acculturation attitudes of 281 Palestinian Arab Christian adolescents in Israel and their perceptions of the expectations held by majority peers regarding their preferred mode of acculturation vis-à-vis two majority groups: Israeli Jews and Muslim Arabs. Findings suggest that Palestinian Arab Christian adolescents in Israel wish to maintain their ingroup identity; however, they expressed more willingness to adopt elements of the Jewish society than did Muslim Arabs. They also feel stronger assimilation pressures coming from Israeli Jews. These results are explained primarily in terms of differences between the two majority groups in their control over valuable resources.